How does Fintech Enable Enterprise Total Factor Productivity? Evidence from Listed Companies in China’s Strategic Emerging Industries - Liu, Mingfei; Wang, Ye; Yin, Zongyi (Transformations In Business & Economics, 2024)
The new round of scientific and technological revolution and industrial transformation has led to new opportunities and challenges for various economic entities. Determining whether the development of financial technology can activate the innovation vitality of strategic emerging industries and improve the total factor productivity of enterprises is a completely new research topic. To explore the pathways available for improving the total factor productivity of enterprises, based on the neo-classical economic growth theory, micro-banking theory, and spillover effect theory,the development level of financial technology (fintech) in China’s prefecture-level cities was measured using the method of determining the annual cumulative number of key word frequencies in the Baidu News.The impact mechanism of fintech on the total factor productivity of these enterprises was examined using data from listed companies in China’s A-share strategic emerging industries from 2010 to 2022. Results show that fintech can significantly promote the improvement of the total factor productivity of listed companies in strategic emerging industries in three ways: easing the financing constraints of enterprises, reducing the agency cost of enterprises, and improving the innovation strategy of enterprises. Fintech has a more obvious effect on the total factor productivity of private enterprises than it does on that of state-owned enterprises. Fintech also plays a stronger role in promoting the total factor productivity of enterprises in coastal areas than in inland areas. The conclusions obtained from this study have important practical guiding significance for ensuring the continuous promotion of fintech innovation and consolidating the long-term mechanism through which fintech serves the real economy.